The Effect of Place Attractiveness, Curiosity, and Lifestyle on Visit Decision in Kavling DPR Sidoarjo - Abidin, Sarah Mauludiyah; Fauziyyah, Salma; Sularso, Raden Andi (Universitas Bunda Mulia, 2023)
The growth of the coffee shop industry as evidence of shifting consumer behavior throughout the pandemic era has encouraged enterprises to constantly innovate new café designs with extraordinary characteristics, one of which is the Kavling DPR Sidoarjo. This study intended to examine how customers decide whether to visit the Kavling DPR Sidoarjo based on place attractiveness and curiosity as well as lifestyle. Purposive sampling was employed by the researcher to select 40 participants for this study in order to obtain the primary data using widely dispersed offline questionnaires. The researcher used the Partial Least Square (PLS) data analysis approach to assess the data after obtaining it. The findings of this study showed that place attractiveness directly, but not significantly, influenced visitors' curiosity in visiting Kavling DPR Sidoarjo. Meanwhile, customers' lifestyle directly and significantly influenced their curiosity in visiting Kavling DPR Sidoarjo. Other findings regarding customers' decision to visit Kavling DPR Sidoarjo revealed that curiosity and lifestyle had a direct and significant impact on it. Meanwhile, place attractiveness had a direct but not significant effect on customers' decision to visit Kavling DPR Sidoarjo. Additionally, subsequent findings show that consumers' curiosity did not significantly moderate the influence of place attractiveness on their choice to visit Kavling DPR Sidoarjo. However, it significantly influenced how customer's lifestyles affected their choice to visit Kavling DPR Sidoarjo.